THE INFLUENCE OF REWARDS AND PUNISHMENTS ON THE STUDENTS' LEARNING MOTIVATION AT GRADE V - Septi Ayu Lestari; Rahmat Aziz; Samsul Susilawati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
Students' low motivation can be caused by how teachers teach in the learning activities. Teachers can use rewards and punishments to trigger students' learning motivation in the classroom. The data were collected through a questionnaire with a Likert scale. Meanwhile, the samples were selected by total sampling. Then, the data were analyzed by using multiple regression analysis to determine the effect of giving rewards and punishments on students' learning motivation either partially or simultaneously. The results showed that the tcount was 0.203 and ttable was 0.306; thus, Ho was accepted and Ha was rejected. As a result, giving rewards had no significant positive effect on students' learning motivation at grade V of SDN Dadaprejo 01, Kecamatan Junrejo, Kota Batu. Hence, partially giving rewards had no significant positive effect on motivation. In addition, this study also obtained that the tcount was 4.552 and the ttable was 0.306. Thus, Ho was rejected and Ha was accepted. This result indicated that punishment had a significant positive effect on the students' learning motivation at grade V of SDN Dadaprejo 01, Kecamatan Junrejo, Kota Batu. Hence, partially, punishment had a significant positive effect on learning motivation.